2007
DOI: 10.1373/clinchem.2006.079814
|View full text |Cite
|
Sign up to set email alerts
|

A Strong Interaction between Serum γ-Glutamyltransferase and Obesity on the Risk of Prevalent Type 2 Diabetes: Results from the Third National Health and Nutrition Examination Survey

Abstract: Background: Some studies have found an association of obesity with type 2 diabetes only among individuals with high normal serum ␥-glutamyltransferase (GGT) activity, not in those with low serum GGT. If this interaction reflected pathophysiology, it would have scientific and clinical importance. The findings failed to reach statistical significance, however, and no articles have focused on the topic. We investigated possible interactions between serum GGT and body mass index (BMI) and their effects on the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 21 publications
5
53
1
1
Order By: Relevance
“…These findings differ from a previous crosssectional report, which, in a large sample of the US population, showed a stronger association between elevated plasma GGT levels and the risk of prevalent diabetes in persons with obesity than in those with a lower BMI [19]. However, as this study was not prospective and considered only newly recognised diabetes, the potential confounding impact of hyperglycaemia on the level of GGT could not be investigated.…”
Section: Discussioncontrasting
confidence: 91%
“…These findings differ from a previous crosssectional report, which, in a large sample of the US population, showed a stronger association between elevated plasma GGT levels and the risk of prevalent diabetes in persons with obesity than in those with a lower BMI [19]. However, as this study was not prospective and considered only newly recognised diabetes, the potential confounding impact of hyperglycaemia on the level of GGT could not be investigated.…”
Section: Discussioncontrasting
confidence: 91%
“…Furthermore, the association between serum GGT and type 2 diabetes was stronger among the obese, and obesity did not predict the risk of type 2 diabetes among participants with GGT levels at the low end of the normal range [1]. A similar pattern of associations was observed in datasets from the Coronary Artery Risk Development in Young Adults (CARDIA) study [2], the Finland Multinational Monitoring of Trends and Determinants in Cardiovascular Disease (FinMONICA) study [3], the National Health and Nutrition Examination Survey (NHANES) [4], and in German women, but not men [5], leading us to search for new interpretations of serum GGT. Cellular GGT, found on the plasma membrane in most tissues [6], metabolises extracellular glutathione (GSH), the main intracellular antioxidant, allowing precursor amino acids to be reutilised for intracellular GSH re-synthesis [7]a process known as the 'γ-glutamyl cycle' (Fig.…”
mentioning
confidence: 56%
“…Many investigators recommend measurements of plasma enzymes to test for FLHS (Diaz et al, 1999;Walzem et al, 1993) and suggest that enzyme activities are indicative of liver damage in birds, in particular AST, LDH, and GDH. In this study, GGT was measured as it is a more sensitive and specific indicator of liver dysfunction in mammals and birds (Center, 2007;Lim et al, 2007). From studies in humans and animals it has been shown that there is a correlation between GGT and TG in patients with steatohepatitis (Lim et al, 2007;Sakugawa et al, 2004).…”
Section: Discussionmentioning
confidence: 95%